Design, Synthesis and Antimicrobial Activity Screening of Novel Cyclic Imides Derived From Heterocyclic Imines - Akol, Raghad Naeem; Al-Azzawi, Ahlam Marouf (Iraqi Journal of Science, 2025)
In this work, nine new cyclic imides 10-18 were synthesized starting with 4-aminoacetophenone and heterocyclic amines (2-aminothiazole, 4-aminopyridine, and 4-aminoantipyrine). The first step included a condensation between 4-aminoacetophenone and heterocyclic amines to afford the corresponding imines 1-3 in 82-90% yields. These imines (1-3) were then treated with phthalic and maleic anhydrides to give heterocyclic iminophthalamic and maleamic acids 4-9, which were dehydrated using fusion conditions to provide the desired phthalimides and maleimides (10-15) in yields ranging from 75 to 92%. Heterocyclic imino tetrachlorophthalimides 16-18 were synthesized (83-88% yields) in a one-pot procedure via the reaction of imines 1-3 with tetrachlorophthalic anhydride in the presence of glacial acetic acid as a catalyst. Results indicated that the prepared cyclic imides (1-3) exhibit good antimicrobial activity.